PROMOSI PERILAKU SEHAT ANTISIPASI DIRI (PERISAI) KEPADA KADER MASYARAKAT DESA KANDANGAN GRESIK - Ni Ketut Alit Armini (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Community empowerment in healthy behaviour can be started from the family (household) as the smallest unit of society which has strategic value in the implementation of health development. Important efforts need to be made by providing understanding to increase awareness in implementing a clean and healthy lifestyle, especially in the Covid-19 pandemic situation. This community service program supported by LPPM and the Faculty of Nursing, Universitas Airlangga aims to increase public awareness about the adaptation of new habits in the Covid-19 pandemic era and implement clean and healthy living habits from a family structure. The activity was carried out in the village area of Kandangan, Cerme District, Gresik Regency. The enthusiastic device provided support for activities involving 2 midwives and 35 cadres. The activity method is in the form of interactive counselling to posyandu cadres with lectures, discussions, demonstrations, and evaluations. The results of the activity showed that the cadres who participated in the activity had a good level of knowledge (77.14%) and most of the attitudes were positive (91.4%). Demonstration of how to use a mask and six steps of washing hands are well followed. It is necessary to increase community resilience during the Covid-19 pandemic through healthy behaviours of self-anticipation (PERISAI ) by fostering good health values in the family.